علاقة القصاص والدية بمقاصد الشريعة: دراسة تحليلية = The relationship between qisas, diyyat and the objectives of syariah: an analytical study - Muhammad Husni, Ahmad; Niteh, Muhammad Yosef; Ahmad, Maad (Pusat Pengajian Teras, Kolej Universiti Islam Selangor (KUIS), 2016)
يعترب القصاص يف الشريعة اإلسالمية من أكرب وأهم العوامل الستقرار العدل يف اجملتمع واألمن يف ً االحتفاظ بكرامة اإلنسان وحريته، فلوال القصاص ألهلك الناس بعضهم نفوس الناس، وفيه أيضا .ً بعضا والقصاص يهدف إىل حتقيق املساواة بني اجلرمية والعقوبة حبيث تكون العقوبة مساوية للجرمية املرتكبة كما مياثل القصاص العقوبة الرادعة اليت تنتظر اجملرم الذي ردع اجملين عليه وأولياءه واجملتمع الذي يعيش فيه هبذه اجلرمية البشعة، وابإلضافة إىل هذه املعاين، فإن القصاص يشفي غيظ اجملين عليه، وغيظ أوليائه. هنجت هذه الدراسة املنهج االستقرائي التحليلي جلمع آراء الفقهاء والباحثني وأدلتهم وحججهم حول املوضوع، والنصوص املتعلقة به حماوالً حتليلها حتليالً أصوليا وفقهيا مبا يناسب واقعنا املعاصر ومقاصد الشريعة. فخلصت الدراسة على أن الشريعة اإلسالمية وضعت تشريعات حكيمة للمحافظة على أنفس الناس و أطرافهم من االعتداء عليها، ً يف أعلى درجات اجلزاء وهو القتل و جعلت لويل املقتول حق فجعلت عقاب من يقتل متعمدا العفو جماانً – دية خمففة- أو على بدل من املال )الدية(، ورتبت على قتل اخلطأ بعض العقوابت اليت جتعل اإلنسان يراعي يف تصرفاته وأفعاله. وهو الذي حيقق مقصد الشريعة يف احلفاظ على النفوس. ********************************************************* Qisas (the law of retaliation) in Islamic law is considered as the most important factor to secure the lives of the people, and in turn creating justice within the society. It also preserves human dignity and freedom. The punishment will cleanse the offender from the sins he has committed, and give chance to others to live. Without qisas, people would destroy each other through hostility, hatred and revenge. Hence to avoid from this kind of damage and to secure the lives of the people, Islamic law has placed the qisas punishment. This law of retaliation is aimed to achieve the equality between the crimes and the sentence so that the penalty shall be equal to the crime committed and to deter the criminal who had terrified the victim and his community. In addition, qisas will heal the rage of the victim and the family. This study has adopted the inductive analytical approach to gather the views of scholars and researchers, and their evidences and arguments on the subject. This study is also to gather and analyze the texts related to qisas using the Principle of Fiqh and Usul Fiqh according to the objectives of Islamic Law. This study has found that the Islamic Law has placed a wise legislation to preserve the souls and limbs of the people. In qisas, the highest punishment for murder convictions would draw the harshest punishment which is death sentence. However, the victim’s family is given a choice either to forgive the murderer or to request for diyyat (compensation payment), and the Islamic Law has also set a simple diyyat for those who killed unintentionally. This is to make the human more careful in his actions and from being ignorant towards criminal matters. This rule is to realize one of the main objectives of syariah which is to preserve human lives